Impact of fluconazole susceptibility on the outcome of patients with candidaemia: data from a population-based surveillance. (September 2017) - Fernández-Ruiz, M.; Guinea, J.; Lora-Pablos, D.; Zaragoza, Ó.; Puig-Asensio, M.; Almirante, B.; Cuenca-Estrella, M.; Aguado, J.M.; ,; ,
Abstract: Objectives: The clinical correlation of fluconazole antifungal susceptibility testing (AST) for Candida isolates and its integration with pharmacokinetics/pharmacodynamics (PK/PD) parameters is unclear. We analysed the impact of fluconazole minimum inhibitory concentration (MIC) values, 24-hour area under the concentration–time curve (AUC24 ) and AUC24 /MIC ratio on the outcome of candidemic patients. Methods: We included 257 episodes of candidaemia treated with fluconazole monotherapy for ≥72 hours from a population-based surveillance conducted in 29 hospitals (CANDIPOP Project). AST was centrally performed by European Committee on Antimicrobial Susceptibility Testing (EUCAST) and Clinical and Laboratory Standards Institute (CLSI) microdilution methods. Primary outcome was clinical failure (30-day mortality and/or persistent candidaemia for ≥72 hours from initiation of therapy). Secondary outcomes included early (3–7 days) and late (3–30 days) mortality. Results: Rates of clinical failure, early and late mortality among evaluable episodes were 32.3% (80/248), 3.1% (8/257) and 23.4% (59/248). There was no relationship between fluconazole MIC values or PK/PD parameters and clinical failure. Although MIC values ≥2 mg/L by EUCAST (positive predictive value 32.1%, negative predictive value 68.7%) and ≥0.5 mg/L by CLSI (positive predictive value 34.8%, negative predictive value 74.4%) appeared to be optimal for predicting clinical failure, no significant associations remained after multivariate adjustment (odds ratio 1.67; 95% confidence interval 0.48–5.79; p 0.423). Lack of association was consistent for alternative thresholds (including proposed clinical breakpoints). The only association found for secondary outcomes was between an AUC24 /MIC ratio >400 h by CLSI and early mortality (odds ratio 0.18; 95% confidence interval 0.04–0.98; p 0.026). Conclusions: High fluconazole MIC values did not negatively impact outcome of patients with candidaemia treated with fluconazole. No effect of PK/PD targets on the risk of clinical failure was found.